Additively manufactured mesh-type titanium structures for cranial implants: E-PBF vs. L-PBF. (1st January 2021) - Lewin, Susanne; Fleps, Ingmar; Åberg, Jonas; Ferguson, Stephen J.; Engqvist, Håkan; Öhman-Mägi, Caroline; Helgason, Benedikt; Persson, Cecilia
Abstract: A patient-specific titanium-reinforced calcium phosphate (CaP–Ti) cranial implant has recently shown promising clinical results. Currently, its mesh-type titanium structure is additively manufactured using laser beam powder bed fusion (L-PBF). Nevertheless, an electron-beam (E-PBF) process could potentially be more time efficient. This study aimed to compare the geometrical accuracy and mechanical response of thin titanium structures manufactured by L-PBF (HIPed) and E-PBF (as-printed). Tensile test (ø = 1.2 mm) and implant specimens were manufactured. Measurements by μCT revealed a deviation in cross-sectional area as compared to the designed geometry: 13–35% for E-PBF and below 2% for L-PBF. A superior mechanical strength was obtained for the L-PBF specimens, both in the tensile test and the implant compression tests. The global peak load in the implant test was 457 ± 9 N and 846 ± 40 N for E-PBF and L-PBF, respectively. Numerical simulations demonstrated that geometrical deviation was the main factor in implant performance and enabled quantification of this effect: 34–39% reduction in initial peak force based on geometry, and only 11–16% reduction based on the material input. In summary, the study reveals an uncertainty in accuracy when structures of sizes relevant to mesh-type cranial implants are printed by the E-PBF method. Graphical abstract: Unlabelled Image Highlights: The study compares two additive manufacturing processes for mesh-type cranial implants, HIPed L-PBF and as-printed E -PBF. The HIPed L-PBF specimens showed superior mechanical strength in both the material (47%) and implant testing (87%). Geometrical deviations were obtained for the as-printed E-PBF implants (13–35%). The effect of geometrical deviations on implant performance was quantified, as enabled by mechanical simulations.